Fermentação controlada de Bourbon vermelho com leveduras comerciais - Araújo, Shismany de Fátima Assunção (2022)
Brazil is the largest producer and exporter of coffee in the world, contributing favorably to the surplus in the national balance of trade. Increasing the final quality of the beverage results in increased profit for producers, as the search for specialty coffees increases every day. The type of post-harvest processing affects the sensory characteristics of the beverage, especially the fermentation process directly impacts the quality of the beverage. The objective was to evaluate the fermentation process of Bourbon Vermelho coffee by two commercial yeasts, S. cerevisiae FX10, which highlights the characteristics of the coffee terroir and RX60, which contributes to the formation of aromatic compounds such as fruity ones. This dissertation also studied the physicochemical characteristics of the cultivar Bourbon Vermelho produced in the Cerrado Mineiro region in Patos de Minas-MG in the 2019/2020 and 2020/2021 harvests, harvested mechanically, manually, using cherry fruits and peeled cherry fruits. The characterization of the fruits in the two harvests detected significant differences between the levels of moisture, ashes, proteins, lipids and total acidity between the harvests and the type of coffee processing, which corroborates the available literature, since it mentions that there may be a difference significant among fruit constituents, as these are dependent on environmental and nutritional factors, harvesting and processing method. Fermentation capacity was carried out to evaluate the behavior of two commercial Saccharomyces cerevisiae strains FX10 and RX60 in the coffee husk and pulp medium, producing metabolites such as ethanol, glycerol, and organic acids. Induced anaerobic solid-state fermentations (SIAF) were carried out using the two yeasts FX10 and RX60 in red Bourbon coffees under process conditions established by a Central Composite Rotational Design (DCCR) evaluating the influence of temperature and time on the production of organic acids, alcohols and in the sensorial characteristics of the drink. Sensory analyzes were performed according to the Specialty Coffee Association — SCA methodology. During fermentation, citric, malic, succinic, and acetic acids were detected in all experiments. In the sensory evaluation, all coffees inoculated with FX10 and RX60 yeasts obtained scores from 82 to 85 points, scores obtained above the control fermentations without the use of inoculum, which obtained scores between 80 to 82 points, whereas the coffees that did not undergo the established fermentation process, called control, obtained 81 points in the cup test. The aroma, sweetness, uniformity, and clean cup attributes obtained the maximum score, characterizing a standardization of the coffee beverage and the absence of defects. Therefore, the commercial yeasts FX10 and RX60 are considered promising for obtaining coffees with special quality.